Factors that interfere in maternal perception of security at postpartum - Catarina Sousa Silva; Sónia Brandão; Ana Rita Azevedo; Ana Paula Prata (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to identify the factors and variables that interfere with the maternal perception of security at postpartum. Methods: a cross-sectional study, carried out in three Portuguese hospital units, with a non-probabilistic sample of 352 puerperal women, recruited from the postpartum units on the day of hospital discharge after delivery. Maternal sociodemographic and obstetric characteristics, as well as data on monitored pregnancy, childbirth and infant feeding, were collected through the application of a questionnaire developed by the researchers. For the analysis of maternal perception of security, the instrument "Parents' postnatal sense of security" (PPSS) was used. Descriptive and inferential statistics were used for data analysis. Results: women who lived with their partner (t (349) = - 2.34, p=0.020), were multiparous (t (349) = - 2.26, p=0.025), had pregnancy monitored (t (349) = -3.25, p=0.001), had a positive childbirth experience (F (1, 351) = 7.07, p=0.008) and those who exclusively breastfed during hospitalization (F (2, 351) = 11,43, p<0.001), presented greater perception of security at postpartum. Conclusions: the factors that affect the maternal perception of security at postpartum are cohabitation with a partner, parity, monitored pregnancy, childbirth experience and infant feeding. Defining which factors interfere with maternal security at postpartum may contribute to the construction of intervention programs that promote the maternal perception of security at the time of hospital discharge after delivery.